Língua inglesa no ensino multisseriado: tarefas e aprendizagem colaborativa - Ujfalusi, Ezilce Casagrande (2023)
This study aims to investigate the relationship between the multi-grade environment and the teaching of English language through tasks, taking as a theoretical framework the multi-grade teaching (LITTLE, 2001; 2004; 2005), group work, and collaborative learning, in view of Vygotsky's sociocultural theory (1991; 1993), as well as its implications in language teaching and learning (DONATO, 1994; 2004; DAVIN; DONATO, 2013 and FIGUEIREDO, 2019; 2020), through the task-based approach (WILLIS, 1996; WILLIS; WILLIS, 2007 e XAVIER, 2012; 2016). Considering my own teaching practice in a private school in the interior of the state of São Paulo, where 6th and 7th-grade students are grouped in the same classroom, we start from the premise that collaborative group work can contribute to the process of learning the English language. During interactions among peers, active participation of students was observed, as they engaged in negotiations and reflections on the language, playing a significant role in the joint construction of knowledge and fostering personal development both for themselves and their peers. The study, configured as a case study, was conducted through questionnaires, the application of a task, and a research diary maintained by the teacher-researcher. Through these instruments, we obtained data that allowed us to outline the reality of interactions in a multi-grade classroom. We sought to answer the following question: What relationship can be established between the multi-grade environment and the teaching of the English language through tasks? By exploring the multiple variables involved in this environment, we hope that this work can contribute to the reflection on the development of pedagogical practices that enable students of different ages and knowledge levels to learn from each other through a participatory, critical, and reflective formation, not only understanding the learning process in which they are engaged but also utilizing the acquired knowledge, mobilizing resources to solve emerging situations.